A Comparison of Vacuum Infusion, Vacuum Bagging, and Hand Lay-Up Process on The Compressive and Shear Properties of GFRP Materials - Abdurohman, Kosim; Pratomo, Rezky Agung; Hidayat, Ryan; Ramadhan, Redha Akbar; Nurtiasto, Taufiq Satrio; Ardiansyah, Riki; P.P.P., Mikhael Gilang (Indonesian Journal of Aerospace, 2023)
Fiber-reinforced plastics are widely used in aerospace, marine, military, automotive, wind turbine, sports, and civil engineering applications. GFRP is a common material used in engineering applications such as for UAV structural material. Several techniques that can be used in the composite structure manufacturing process are HLU, VB, and, VARI. This paper studies the influence of the three manufacturing processes on the compressive and shear properties of GFRP composites. This study uses e-glass fiber as reinforcement material and a clear epoxy polymer called lycal as matrix material. The composites were manufactured by using HLU, VB, and VARI processes. The specimen dimensions, compressive, and shear tests are following ASTM standards. The microstructural characteristics were observed using a scanning electron microscope. The compressive strength of VARI composite is higher than HLU and VB composites up to 71% and 53%, respectively. The shear strength of the VARI composite is higher than HLU and VB composites up to 71% and 53%, respectively.